High Incidence of Osteoarthritis Observed in Patients at Short- to Midterm Follow-Up after Delayed Multiligament Knee Reconstruction - Sobrado, Marcel Faraco; Giglio, Pedro Nogueira; Bonadio, Marcelo Batista; Pecora, Jose Ricardo; Gobbi, Riccardo Gomes; Angelini, Fabio Janson; Helito, Camilo Partezani (The Journal of Knee Surgery, 2021)
The aim of this study was to evaluate the incidence of knee osteoarthritis, failure rate of reconstruction, and clinical outcomes of patients with chronic multiligament knee injuries subjected to surgical treatment. Sixty-two patients with chronic knee dislocation subjected to multiligament reconstruction between April 2008 and July 2016 were evaluated, with a minimum follow-up of 24 months. Anteroposterior and lateral radiographs were performed in the pre- and last postoperative evaluation; the progression of degenerative changes according to the Kellgren-Lawrence classification (KL) was assessed. The Schenck classification, Knee Injury and Osteoarthritis Outcome Score (KOOS), time between injury and surgery, type of postoperative rehabilitation protocol (brace vs. external fixator), and physical examination for ligament instability were also evaluated. Univariate and multivariate analysis were performed, p <0.05 was considered significant. Fifty-two (83.9%) patients were men and 16.1% (n = 10) were women, with a mean age of 38.8 ± 1.3 years. The time from injury to surgery was 31.1 ± 6.1 months, and the follow-up time was 6.1 ± 0.5 years. The mean final KOOS was 79.3 ± 10.4 and the overall reconstruction failure occurred in 25.8%. Of all patients, 64.5% (n = 40) presented a KL classification of ≥2 and were defined as having radiographic osteoarthritis (OA). As 11.7% (n = 7) also presented arthritis in the contralateral knee, in 53.2% (n = 33) the progression was most likely due to the initial injury. The failure of ligament reconstruction or residual instability was present in 15 (35.7%) of patients with OA, and only one patient (4.5%) without OA. In the multivariate analysis, only reconstruction failure was an independent predictor of OA (odds ratio = 13.2 [p = 0.028]). There is a high incidence of knee OA following ligament reconstruction for chronic multiligament knee injuries. Ligament reconstruction failure was the only independent predictor for the development of OA in our study.
Keywords: knee dislocation; multiple ligament knee injury; osteoarthritis; chronic ligament injury